Immunohistochemical expression of hedgehog proteins in diffuse large B-cell lymphoma - Azman, Siti Nur Lina (2016)
The Hedgehog (Hh) signalling pathway is a developmental signalling pathway involved in numerous developmental processes, including determination of cell fate, proliferation, patterning, survival and differentiation. In most adult tissues, this pathway remains silent and its aberrant activation has been documented in various types of malignancies including basal cell carcinoma, gastrointestinal, lung and prostate cancers. The aim of this study was to demonstrate the expression of Hh signalling pathway components in 107 DLBCL formalin fixed paraffin embedded (FFPE) tissues from Hospital Kuala Lumpur and determine their association with clinicopathological parameters. We assessed the expression of SHH (ligand), GLI1 (transcriptional effectors of SHH signalling), its receptor Patched (PTCH1) and signal transducer Smoothened (SMO) using immunohistochemistry. SHH was expressed in 42 (42.1%) cases, GLI1 in 61 (57%) cases, PTCH1 in 107 (100%) cases and SMO in 105 (98.1%) cases. Tumours display strong staining intensity for SMO and PTCH1 but low intensity for SHH and GLI1 when compared to normal tonsil tissues. Immunohistochemical staining results showed that SHH, GLI1 and SMO proteins were localised in the cytoplasm of tumour cells, whereas PTCH1 was mainly localised in their nucleus of tumour cells. Survival curves calculated using the Kaplan-Meier method also showed no significant association with sociodemographic distributions (age, gender, race, tumour involvement) and expression between HH signalling pathway proteins. To the best of our knowledge, there is no study investigating the correlation between SHH, PTCH1 and SMO. This study has shown that SHH expression was significantly associated with the expression of PTCH1 (P=0.030) and PTCH1 was significantly associated with SMO (P=0.030) expression. Our findings suggest that high expression of PTCH1 and SMO might be important in the pathogenesis of DLBCL. However, further studies are required to ascertain their roles in DLBCL.